1992
DOI: 10.1159/000139008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Inhibitory Effects of Dihydropyridines on Platelet Aggregation, Calcium Uptake and Cyclic AMP Concentration

Abstract: We studied the in vitro effects of several calcium channel blockers from the dihydropyridine (DHP) family on platelet aggregation and endogenous serotonin secretion, calcium uptake and cyclic AMP (cAMP) concentration using washed rat platelets. We found that, after 1 min incubation, nifedipine (Nil), nitrendipine (Nit) and nisoldipine (Nis) inhibited the thrombin-induced platelet aggregation and serotonin secretion with IC50 of about 140, 5 and 2 μmol/l, respectively. Nis and Nit are thus much more active than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In the previous 2 decades, several investigators have raised concern about possible prohemorrhagic activity of CCBs, citing an association between use of CCBs and the occurrence of cerebral, surgical, or gastrointestinal (GI) hemorrhage . Laboratory studies have also suggested that both dihydropyridine and nondihydropyridine CCBs impair platelet activity, providing a possible mechanistic basis for the putative prohemorrhagic activity of CCBs …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous 2 decades, several investigators have raised concern about possible prohemorrhagic activity of CCBs, citing an association between use of CCBs and the occurrence of cerebral, surgical, or gastrointestinal (GI) hemorrhage . Laboratory studies have also suggested that both dihydropyridine and nondihydropyridine CCBs impair platelet activity, providing a possible mechanistic basis for the putative prohemorrhagic activity of CCBs …”
mentioning
confidence: 99%
“…[12][13][14][15][16][17] Laboratory studies have also suggested that both dihydropyridine and nondihydropyridine CCBs impair platelet activity, providing a possible mechanistic basis for the putative prohemorrhagic activity of CCBs. [18][19][20][21] Nevertheless, the evidence regarding risk of bleeding associated with CCBs is inadequate for several reasons. First, there is a lack of randomized clinical trial evidence supporting the association between CCBs and GI hemorrhage, relative to other classes of antihypertensive agents.…”
mentioning
confidence: 99%
“…Apart from the usual reported adverse reactions of CCBs, there is a possibility of an increased risk of gastrointestinal bleeding (GIB) due to their potential anti‐platelet effect. This is further supported by animal, in vivo and ex vivo studies that demonstrated the inhibition of platelet aggregability of CCBs in putative pro‐haemorrhagic activity . The promotion of vasodilation by CCBs also opposes the usual vasoconstriction response to bleeding .…”
Section: Introductionmentioning
confidence: 69%
“…These parallel changes of wall shear stress and platelet aggregatory responses after nitrendipine treatment could have resulted from simultaneous effects of the Ca2+-antagonist on platelets, vascular smooth muscle and endothelial cells. Some authors have indeed reported a direct effect of high dihydropy ridine concentrations on platelet Ca2+ metabolism (43). However, the presence of dihydropyridine-sensitive voltage-dependent Ca2+ channels in human platelets remains controversial (44,45).…”
Section: Discussionmentioning
confidence: 99%